Correction: Comparative aerobiological study between two stations located at different points in a coastal city in Southern Spain - R. Ruiz‑Mata; M. M. Trigo; M. Recio; E. de Gálvez‑Montañez; A. Picornell (Aerobiologia, 2026)

Geoarchaeology at La Sima Cave. A multi-analysis approach to the Middle Paleolithic during MIS 3 in southern Iberia - J.A. Caro-Gómez; C. Borja-Barrera; E.J. Medina-Luque; M. Cañete-Gómez; G. Álvarez-García; F. Díaz del Olmo; J.M. Recio-Espejo; J.A. Riquelme-Cantal; A. Ruiz-Expósito; J.M. Garrido-Anguita (Quaternary International, 2026)

Application of error-corrected sequencing technologies for in vivo regulatory mutagenicity assessment - Carole L. Yauk; Anthony M. Lynch; Vasily N. Dobrovolsky; Maik Schuler; Stephanie L. Smith-Roe; Devon Fitzgerald; Jake Higgins; Naveed Honarvar; Frank Le Curieux; Shoji Matsumura; Sheroy Minocherhomji; Leslie Recio; et al. (Regulatory Toxicology and Pharmacology, 2026)

Eco-friendly decolorization of Indigo Carmine and Safranine-T dyes with bioenergy generation using a single-chamber microbial fuel cell - M. T. Ritter; M. E. Nagel-Hassemer; D. D. Silveira; R. Moraes; M. Á. Lobo-Recio (International Journal of Environmental Science and Technology, 2025)

Effects of feed additives in the diet of male dairy beef calves on physiological status and rumen microbial fermentation pre- and postweaning - E. Romera-Recio; E. Ramos-Morales; A. Belanche; M. Hassan; P. Romero; A. Gómez; I. Rivelli; N. Llanes; J. Torra; D.R. Yáñez-Ruiz (Animal Feed Science and Technology, 2025)

Flowering seasonality and airborne pollen recent trends in Sierra de las Nieves, the southernmost National Park in continental Spain - Enrique de Gálvez-Montañez; M. Mar Trigo; Marta Recio; Antonio Picornell (Agricultural and Forest Meteorology, 2024)

Revisiting the mercury cycle in marine sediments: A potential multifaceted role for Desulfobacterota - Blanca Rincón-Tomás; Anders Lanzén; Pablo Sánchez; Mónica Estupiñán; Isabel Sanz-Sáez; M. Elisabete Bilbao; Diana Rojo; Iñaki Mendibil; Carla Pérez-Cruz; Marta Ferri; Eric Capo; Ion L. Abad-Recio; et al. (Journal of Hazardous Materials, 2024)

Pollen recognition through an open-source web-based system: automated particle counting for aerobiological analysis - Antonio Jesús Chaves; Cristian Martín; Luis Llopis Torres; Manuel Díaz; Rocío Ruiz-Mata; Enrique de Gálvez-Montañez; Marta Recio; M. Mar Trigo; Antonio Picornell (Earth Science Informatics, 2024)
Airborne pollen is produced by plants for their sexual reproduction and can have negative impacts on public health. The current monitoring systems are based on manual sampling processes which are tedious and time-consuming. Due to that, pollen concentrations are often reported with a delay of up to one week. In this study, we present an open-source user-friendly web application powered by deep learning for automatic pollen count and classification. The application aims to simplify the process for non-IT users to count and classify different types of pollen, reducing the effort required compared to manual methods. To overcome the challenges of acquiring large labelled datasets, we propose a semi-automatic labelling approach, which combines human expertise and machine learning techniques. The results demonstrate that our approach significantly reduces the effort required for users to count and classify pollen taxa accurately. The model achieved high precision and recall rates ( $$\varvec{>96%}$$ > 96 % mAP@0.5), enabling reliable pollen identification and prediction.

Effects of climate change on Platanus flowering in Western Mediterranean cities: Current trends and future projections - Antonio Picornell; José M. Maya-Manzano; Marta Fernández-Ramos; Juan J. Hidalgo-Barquero; Raúl Pecero-Casimiro; Rocío Ruiz-Mata; Enrique de Gálvez-Montañez; María del Mar Trigo; Marta Recio; Santiago Fernández-Rodríguez (Science of The Total Environment, 2024)

LP-57: Increasing Confidence in New Approach Methodologies for Inhalation Risk Assessment with Multiple End Point Assays Using 5-day RepeatExposure to 1,3-dichloropropene - I. Paudel; R. Barutcu; R. Samuel; M. Moreau; S. Slattery; J. Scaglione; L. Recio (Toxicology Letters, 2023)

Study of the cross-talk between Fasciola hepatica juveniles and the intestinal epithelial cells of the host by transcriptomics in an in vitro model - David Becerro-Recio; Judit Serrat; Marta López-García; María Torres-Valle; Francisco Colina; Iván M. Fernández; Javier González-Miguel; Mar Siles-Lucas (Veterinary Parasitology, 2023)

Early microRNA responses in rodent liver mediated by furan exposure establish dose thresholds for later adverse outcomes - Gail M. Nelson; Gleta K. Carswell; Carol D. Swartz; Leslie Recio; Carole L. Yauk; Brian N. Chorley (Toxicology Letters, 2023)

Drivers of variability in Blue Carbon stocks and burial rates across European estuarine habitats - Inés Mazarrasa; Joao M. Neto; Tjeerd J. Bouma; Tim Grandjean; Jordi Garcia-Orellana; Pere Masqué; María Recio; Óscar Serrano; Araceli Puente; José A. Juanes (Science of The Total Environment, 2023)

A comprehensive review of nitrogen removal in an electro-membrane bioreactor (EMBR) for sustainable wastewater treatment - A. C. Sorgato; T. C. Jeremias; M. Á. Lobo-Recio; F. R. Lapolli (International Journal of Environmental Science and Technology, 2023)

Comparative aerobiological study between two stations located at different points in a coastal city in Southern Spain - R. Ruiz-Mata; M. M. Trigo; M. Recio; E. de Gálvez-Montañez; A. Picornell (Aerobiologia, 2023)

Applying wind patterns and land use to estimate the concentrations of airborne pollen of herbaceous taxa in a statistical framework - Antonio Picornell; Rocío Ruiz-Mata; Jesús Rojo; Jose Oteros; Marta Recio; Enrique de Gálvez-Montañez; M. Mar Trigo (Urban Climate, 2023)

Invited review: Novel methods and perspectives for modulating the rumen microbiome through selective breeding as a means to improve complex traits: Implications for methane emissions in cattle - O. González-Recio; M. Martínez-Álvaro; Francesco Tiezzi; A. Saborío-Montero; C. Maltecca; R. Roehe (Livestock Science, 2023)

In vitro digestibility of dietary proteins and in vitro DIAAS analytical workflow based on the INFOGEST static protocol and its validation with in vivo data - Raquel Sousa; Isidra Recio; Dominique Heimo; Sébastien Dubois; Paul J. Moughan; Suzanne M. Hodgkinson; Reto Portmann; Lotti Egger (Food Chemistry, 2023)

The Faja Eruptiva of the Eastern Puna and the Sierra de Calalaste, NW Argentina: U–Pb zircon chronology of the early Famatinan orogeny - C. Casquet; P. Alasino; C. Galindo; R. Pankhurst; J. Dahlquist; E. G. Baldo; C. Ramacciotti; S. Verdecchia; M. Larrovere; C. W. Rapela; C. Recio (Journal of Iberian Geology, 2021)

Implementation of a Low-Cost Quality Improvement Intervention Increases Adherence to Cancer Screening Guidelines and Reduces Healthcare Costs at a University Medical Center - Alejandro Recio-Boiles; Michael Karass; Jose N. Galeas; Vineeth Sukrithan; Andrew H. Gutwein; Hani M. Babiker (Journal of Cancer Education, 2020)

The use of cyclohexane as new solvent for airborne pollen sampling - D. Gharbi; M. M. Trigo; M. Recio (Aerobiologia, 2019)

Application of low-density electric current to performance improvement of membrane bioreactor treating raw municipal wastewater - A. A. Battistelli; T. J. Belli; R. E. Costa; N. M. Justino; D. D. Silveira; M. A. Lobo-Recio; F. R. Lapolli (International Journal of Environmental Science and Technology, 2019)

Can dynamic in vitro digestion systems mimic the physiological reality? - D. Dupont; M. Alric; S. Blanquet-Diot; G. Bornhorst; C. Cueva; A. Deglaire; S. Denis; M. Ferrua; R. Havenaar; J. Lelieveld; A. R. Mackie; M. Marzorati; et al. (Critical Reviews in Food Science and Nutrition, 2019)

Correlation between in vitro and in vivo data on food digestion. What can we predict with static in vitro digestion models? - T. Bohn; F. Carriere; L. Day; A. Deglaire; L. Egger; D. Freitas; M. Golding; S. Le Feunteun; A. Macierzanka; O. Menard; B. Miralles; A. Moscovici; et al. (Critical Reviews in Food Science and Nutrition, 2018)

Seasonal and latitudinal variation in seagrass mechanical traits across Europe: The influence of local nutrient status and morphometric plasticity - L. M. Soissons; M. M. van Katwijk; G. Peralta; F. G. Brun; P. G. Cardoso; T. F. Grilo; B. Ondiviela; M. Recio; M. Valle; J. M. Garmendia; F. Ganthy; I. Auby; et al. (Limnology and Oceanography, 2018)
Seagrasses are marine flowering plants distributed worldwide. They are however threatened, mostly due to the increase of human activities. Seagrasses have the capacity to adapt their morphological, physiological, and mechanical traits to their local conditions. Mechanical traits have been identified as a good tool to investigate a plant‐species capacity to withstand physical forces or disturbances but are still sparsely studied in seagrasses. With this study, we aimed to assess how the mechanical traits of a broadly spread seagrass species vary along a latitudinal gradient in relation to its morphometric plasticity and nutrient status. We found that seagrasses acclimate their mechanical traits in relation to their physiological or morphological traits, both over the growing season and across a latitudinal range: leaves were weaker and thinner in northern areas, particularly at the end of the growing season. Besides the influence of the latitudinal gradient, leaf mechanical strength and stiffness were both strongly affected by their morphometric plasticity. Moreover, we showed that leaves mechanical traits change depending on their nutrient status: leaves were stronger and stiffer in oligotrophic conditions as compared to more eutrophic conditions. Thus, our results imply that, under eutrophication, leaves become weaker and thus more vulnerable to physical forces. This vulnerability is higher in the north at the end of the growing season. The latter is consistent with the more ephemeral character of northern seagrass meadows, in contrast to the more evergreen southern meadows.

Pollen limitation may be a common Allee effect in marine hydrophilous plants: implications for decline and recovery in seagrasses - B. I. Van Tussenbroek; L. M. Soissons; T. J. Bouma; R. Asmus; I. Auby; F. G. Brun; P. G. Cardoso; N. Desroy; J. Fournier; F. Ganthy; J. M. Garmendia; L. Godet; et al. (Oecologia, 2016)

Longitudinal evaluation of hepatitis C viral persistence in HIV-infected patients with spontaneous hepatitis C clearance - A. Rivero-Juarez; A. Caruz; L. M. Real; L. Martinez-Dueñas; F. J. Marquez; M. Frias; E. Recio; A. Gordon; J. A. Pineda; A. Rivero; A. Camacho (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Understanding home range behaviour and resource selection of invasive common brushtail possums (Trichosurus vulpecula) in urban environments - A. L. Adams; M. R. Recio; B. C. Robertson; K. J. M. Dickinson; Y. van Heezik (Biological Invasions, 2013)

Quantifying fine-scale resource selection by introduced European hedgehogs (Erinaceus europaeus) in ecologically sensitive areas - Mariano Rodriguez Recio; Renaud Mathieu; M. Cecilia Latham; A. David M. Latham; Philip J. Seddon (Biological Invasions, 2013)

Antiviral activity of casein and α s2 casein hydrolysates against the infectious haematopoietic necrosis virus, a rhabdovirus from salmonid fish - S Rodríguez Saint‐Jean; A De las Heras; W Carrillo; I Recio; J B Ortiz‐Delgado; M Ramos; J A Gomez‐Ruiz; C Sarasquete; S I Pérez‐Prieto (Journal of Fish Diseases, 2013)
Salmonid fish viruses, such as infectious haematopoietic necrosis virus ( IHNV ), are responsible for serious losses in the rainbow trout and salmon‐farming industries, and they have been the subject of intense research in the field of aquaculture. Thus, the aim of this work is to study the antiviral effect of milk‐derived proteins as bovine caseins or casein‐derived peptides at different stages during the course of IHNV infection. The results indicate that the 3‐h fraction of casein and α S2 ‐casein hydrolysates reduced the yield of infectious IHNV in a dose‐dependent manner and impaired the production of IHNV ‐specific antigens. Hydrolysates of total casein and α S2 ‐casein target the initial and later stages of viral infection, as demonstrated by the reduction in the infective titre observed throughout multiple stages and cycles. In vivo , more than 50% protection was observed in the casein‐treated fish, and the kidney sections exhibited none of the histopathological characteristics of IHNV infection. The active fractions from casein were identified, as well as one of the individual IHNV ‐inhibiting peptides. Further studies will be required to determine which other peptides possess this activity. These findings provide a basis for future investigations on the efficacy of these compounds in treating other viral diseases in farmed fish and to elucidate the underlying molecular mechanisms of action. However, the present results provide convincing evidence in support of a role for several milk casein fractions as suitable candidates to prevent and treat some fish viral infections.

Effect of meteorological parameters on Poaceae pollen in the atmosphere of Tetouan (NW Morocco) - Nadia Aboulaich; Lamiaa Achmakh; Hassan Bouziane; M. Mar Trigo; Marta Recio; Mohamed Kadiri; Baltasar Cabezudo; Hassane Riadi; Mohamed Kazzaz (International Journal of Biometeorology, 2013)

Analysis of parcel-based image classification methods for monitoring the activities of the Land Bank of Galicia (Spain) - T. Hermosilla; J. M. Díaz-Manso; L. A. Ruiz; J. A. Recio; A. Fernández-Sarría; P. Ferradáns-Nogueira (Applied Geomatics, 2012)

Atmospheric pollen dynamics in Münster, north-western Germany: a three-year study (2004–2006) - M. Melgar; M. M. Trigo; M. Recio; S. Docampo; J. García-Sánchez; B. Cabezudo (Aerobiologia, 2012)

Mechanisms involved in the adenosine-induced vasorelaxation to the pig prostatic small arteries - Ana S. F. Ribeiro; Vítor S. Fernandes; Luis M. Orensanz; María Pilar Martínez; Paz Recio; Ana Martínez-Sáenz; Belén Climent; Jose Luis Arteaga; Albino García-Sacristán; Dolores Prieto; Medardo Hernández (Purinergic Signalling, 2011)

Mechanisms involved in the nitric oxide-induced vasorelaxation in porcine prostatic small arteries - Vítor S. Fernandes; Ana Martínez-Sáenz; Paz Recio; Ana S. F. Ribeiro; Ana Sánchez; María Pilar Martínez; Ana Cristina Martínez; Albino García-Sacristán; Luis M. Orensanz; Dolores Prieto; Medardo Hernández (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Pingüino In-bearing polymetallic vein deposit, Deseado Massif, Patagonia, Argentina: characteristics of mineralization and ore-forming fluids - Sebastián M. Jovic; Diego M. Guido; Isidoro B. Schalamuk; Francisco J. Ríos; Colombo C. G. Tassinari; Clemente Recio (Mineralium Deposita, 2011)

Trends in grass pollen season in southern Spain - Herminia García-Mozo; C. Galán; P. Alcázar; C. Díaz de la Guardia; D. Nieto-Lugilde; M. Recio; P. Hidalgo; F. Gónzalez-Minero; L. Ruiz; E. Domínguez-Vilches (Aerobiologia, 2010)

High incidence of Aspergillus and Penicillium spores in the atmosphere of the cave of Nerja (Malaga, southern Spain) - S. Docampo; M. M. Trigo; M. Recio; M. Melgar; J. García-Sánchez; M. C. Calderón-Ezquerro; B. Cabezudo (Aerobiologia, 2010)

The effect of recent climatic trends on Urticaceae pollination in two bioclimatically different areas in the Iberian Peninsula: Malaga and Vigo - Marta Recio; F. Javier Rodríguez-Rajo; M. Victoria Jato; M. Mar Trigo; Baltasar Cabezudo (Climatic Change, 2009)

Identification and relationships of accessions grown in the grapevine (Vitis vinifera L.) Germplasm Bank of Castilla y Léon (Spain) and the varieties authorized in the VQPRD areas of the region by SSR-marker analysis - J. C. Santana; E. Hidalgo; A. I. de Lucas; P. Recio; J. M. Ortiz; J. P. Martín; J. Yuste; C. Arranz; J. A. Rubio (Genetic Resources and Crop Evolution, 2008)

Noradrenergic vasoconstriction of pig prostatic small arteries - Paz Recio; Luis M. Orensanz; María Pilar Martínez; Jorge Navarro-Dorado; Salvador Bustamante; Albino García-Sacristán; Dolores Prieto; Medardo Hernández (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Risk of pollen allergy in Nerja (southern Spain): a pollen calendar - Silvia Docampo; Marta Recio; M. Mar Trigo; Marta Melgar; Baltasar Cabezudo (Aerobiologia, 2007)

Molecular Cloning and Expression of a Kv1.1-like Potassium Channel from the Electric Organ of Electrophorus electricus - W. B. Thornhill; I. Watanabe; J. J. Sutachan; M. B. Wu; X. Wu; J. Zhu; E. Recio-Pinto (The Journal of Membrane Biology, 2003)

Transcription and weak expression of HLA-DRB6 : a gene with anomalies in exon 1 and other regions. - Victor M. Fernandez-Soria; Pablo Morales; Maria J. Castro; Belen Suarez; Maria J. Recio; Miguel A. Moreno; Estela Paz-Artal; A. Arnaiz-Villena (Immunogenetics, 1998)